2010
DOI: 10.1097/mao.0b013e3181dbb7c2
|View full text |Cite
|
Sign up to set email alerts
|

HASTE Diffusion-Weighted 3-Tesla Magnetic Resonance Imaging in the Diagnosis of Primary and Relapsing Cholesteatoma

Abstract: Half-Fourier acquisition single-shot turbo-spin-echo diffusion-weighted magnetic resonance imaging technique, using a 3T unit, may be a diagnostic tool for a rapid and highly reliable discrimination between cholesteatomatous and noncholesteatomatous tissue in the middle ear, with 100% of positive and negative predictive values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 25 publications
5
31
0
2
Order By: Relevance
“…These results are similar to previously published qualitative studies in the literature reporting 100% sensitivity and specificity (22)(23)(24)(25). However, most qualitative non-echoplanar DWI studies in the literature have reported slightly lower sensitivity (82%-92%) and specificity (86%-96%) values (5,6,14,19,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 78%
“…These results are similar to previously published qualitative studies in the literature reporting 100% sensitivity and specificity (22)(23)(24)(25). However, most qualitative non-echoplanar DWI studies in the literature have reported slightly lower sensitivity (82%-92%) and specificity (86%-96%) values (5,6,14,19,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 78%
“…The usefulness of non-EP DWI for detecting patients with incipient disease has been less well-studied. Although excellent previous reports by Pizzini et al, 23 De Foer et al, 26 Profant et al, 27 and Ilıca et al 34 have included primary cholesteatomas among their cases, our research differs in that this was a prospective study that included only retraction pockets with suspicion of cholesteatoma after evaluation by an expert otologic committee. All patients had surgical confirmation, and the data did not include other groups such as recurrent disease.…”
Section: The Role Of Non-echo-planar Diffusion-weighted Mr Imaging Inmentioning
confidence: 75%
“…12 Several studies have been published since 2006 showing promising results for this technique. [18][19][20][21][22][23][24][25][26][27][28] Recently, Li et al 29 summarized these findings in a meta-analysis including 10 articles (342 patients), reporting an overall sensitivity of 94% and specificity of 94%. False-negatives are rare, often caused by motion artifacts or self-evacuating "mural" cholesteatomas, and false-positives are very infrequent.…”
Section: The Role Of Non-echo-planar Diffusion-weighted Mr Imaging Inmentioning
confidence: 99%
“…La sensibilidad y especificidad del estudio fue de 100% para detección de colesteatoma. En el estudio de Pizzini y cols 7 (2010), se evaluaron 30 pacientes con sospecha de colesteatoma adquirido primario o recurrente, realizando RM con secuencia DWI -HASTE con un equipo resonador de 3.0 Tesla. Se obtuvo un VPP y un VPN de 100% tanto para los hallazgos quirúrgicos en cirugía de colesteatoma primario como de colesteatoma recurrente.…”
Section: Discussionunclassified
“…Una limitación existente en el estudio imagenológico de colesteatoma con RM más secuencia DWI -HASTE, son aquellos casos donde existen bolsillos de retracción o colesteatomas con autoevacuación y escaso contenido de queratina, resultando en colesteatomas secos, los que no producen señales de hiperintensidad en el estudio, impidiendo su detección 4,7,8 . De Foer y cols 2 (2007), evaluaron prospectivamente a 21 pacientes con alta sospecha clínica de colesteatoma, mediante RM con secuencia DWI -HASTE, comparando los hallazgos radiológicos con los quirúrgicos, obteniendo una detección imagenológica de colesteatomas con un tamaño igual o mayor a 2 mm.…”
Section: Discussionunclassified